2007
DOI: 10.1039/b714742b
|View full text |Cite
|
Sign up to set email alerts
|

Microfabrication of cavities in polydimethylsiloxane using DRIE silicon molds

Abstract: We present a novel method to create cavities in PDMS that is simple and exhibits wide process latitude allowing control over the radius of curvature to form shallow concave pits or deep spherical cavities.Polydimethylsiloxane (PDMS) is a silicon-based polymer exhibiting tunable mechanical, chemical and optical properties that are widely leveraged in microfluidic and biotechnology applications. Its clear optical properties are especially advantageous for spectroscopic analysis through lab-on-a-chip devices. 1-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 21 publications
0
39
0
Order By: Relevance
“…25 A vacuum-assisted coating ͑VAC͒ technique 25 was used to completely fill the microbubble with liquid and remove any trapped air bubbles. 1X DPBS was pipetted on top of the microbubbles to completely cover the top openings before placing the microbubbles inside a vacuum chamber.…”
Section: E Pdms Microbubblesmentioning
confidence: 99%
See 1 more Smart Citation
“…25 A vacuum-assisted coating ͑VAC͒ technique 25 was used to completely fill the microbubble with liquid and remove any trapped air bubbles. 1X DPBS was pipetted on top of the microbubbles to completely cover the top openings before placing the microbubbles inside a vacuum chamber.…”
Section: E Pdms Microbubblesmentioning
confidence: 99%
“…[21][22][23] Our group recently reported the growth of homogenously sized 3D melanoma aggregates in microbubble compartment arrays 24 that were fabricated using polydimethylsiloxane ͑PDMS͒ gas expansion molding. 25 MCTSs are a frequently used in vitro model of avascular tumor growth and the physiological tumor microenvironment. Avascular tumors occur at early stages of tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has developed a gas expansion molding (GEM) technique for generating microbubbles which are 80-150 μm diameter spherical compartments formed on polydimethylsiloxane (PDMS), a silicone based elastomeric polymer. We showed that arrays of spherical cavities formed on PDMS [7] using this technique can be used for culturing cancer cells as spheroids [8]. The unique geometry of microbubbles allows the cells to rapidly condition their microenvironment by secreting soluble factors to influence their function [9].…”
Section: Editorialmentioning
confidence: 99%
“…Microfluidic channels of circular cross-section were fabricated in PDMS (12). Briefly, PDMS was poured around a straight metal wire of diameter 50 m and allowed to cure.…”
Section: Circular Microchannel Cell Adhesion Assaymentioning
confidence: 99%
“…A lithography mask was designed using AutoCAD LT 2008 (Autodesk) (12). The mask included arrays of rectangular trenches with 100-m circular openings.…”
Section: Multicellular Breast Cancer Cell Line Aggregate Culturesmentioning
confidence: 99%